2012
DOI: 10.4103/0976-500x.103694
|View full text |Cite
|
Sign up to set email alerts
|

Insulin glargine overdose

Abstract: Insulin glargine is a long acting novel recombinant human insulin analogue indicated to improve glycemic control, in adults and children with type 1 diabetes mellitus and in adults with type 2 diabetes mellitus. The time course of action of insulins including insulin glargine may vary between individuals and/or within the same individual. Insulin glargine is given as a 24-h dosing regimen and has no documented half-life or peak effect. Hypoglycemia is the most common adverse effect of insulin, including insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The use of short acting and long acting insulin via subcutaneous, intramuscular and intravenous routes are reported in scientific literature. [6][7][8][9][10] However, this is the first fatal intentional overdose of lispro insulin to be reported. A case of non-fatal lispro insulin overdose was reported by Brvar et al, 13 where prolonged hypoglycaemia developed in the patient after a suicide attempt by subcutaneous injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of short acting and long acting insulin via subcutaneous, intramuscular and intravenous routes are reported in scientific literature. [6][7][8][9][10] However, this is the first fatal intentional overdose of lispro insulin to be reported. A case of non-fatal lispro insulin overdose was reported by Brvar et al, 13 where prolonged hypoglycaemia developed in the patient after a suicide attempt by subcutaneous injection.…”
Section: Discussionmentioning
confidence: 99%
“…Fatal and non-fatal cases of intentional insulin overdose in both diabetics and non-diabetics have been reported in the literature. [2][3][4][5][6][7][8][9] This is more common among diabetics than non-diabetics and a few cases have also been reported in medical and paramedical personnel. 3,8,10 This is due to the ease of access of these drugs and widespread knowledge of how to administer them.…”
Section: Introductionmentioning
confidence: 99%
“…The first suicide committed with insulin was described in 1932 [ 40 ]. The overall suicides among diabetic people, even by purposefully overdosing insulin, are thoroughly analyzed and described in the scientific literature [ 32 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Any chronic disease is a factor, which increases the suicide rate for adults and children.…”
Section: Accidents and Suicidesmentioning
confidence: 99%
“…The incidence of suicidal thoughts is also higher than the rest of the population, which is closely related to the conscientiousness of the therapy [ 12 , 48 ]. One of the factors indicating an increased risk of suicidal behavior is a diagnosed mental illness [ 46 , 50 ]. The relationship between depression and an increased risk of suicide is proven and generally known [ 77 , 78 ].…”
Section: Accidents and Suicidesmentioning
confidence: 99%
“…These substitutions help with stabilization of the molecule, leading to duration of action around 24 hours. However, case reports have shown that overdoses may have hypoglycemic effects for as long as 5 days (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The proposed theories for this prolonged duration of action include the microprecipitation of insulin glargine in the subcutaneous tissue leading to a 'depot' effect (1), down regulation of insulin receptors in target tissues (1), and the latest research showing the formation of an active metabolite, glargine-M1, at the injection site (2).…”
Section: Introductionmentioning
confidence: 99%